Socio-economic inequalities in the use of drugs for the treatment of chronic diseases in Italy - A. Di Filippo; S. Perna; A. Pierantozzi; F. Milozzi; F. Fortinguerra; N. Caranci; L. Moro; N. Agabiti; V. Belleudi; G. Cesaroni; A. Nardi; T. Spadea; et al. (BMC, 2022)
Abstract Background Since the use of medicines is strongly correlated to population health needs, higher drug consumption is expected in socio-economical deprived areas. However, no systematic study investigated the relationship between medications use in the treatment of chronic diseases and the socioeconomic position of patients. The purpose of the study is to provide a description, both at national level and with geographical detail, of the use of medicines, in terms of consumption, adherence and persistence, for the treatment of major chronic diseases in groups of population with different level of socioeconomic position.  Methods A cross-sectional study design was used to define the "prevalent" users during 2018. A longitudinal cohort study design was performed for each chronic disease in new drug users, in 2018 and the following year. A retrospective population-based study, considering all adult Italian residents (i.e. around 50.7 million people aged ≥ 18 years). Different medications were used as a proxy for underlying chronic diseases: hypertension, dyslipidemia, osteoporosis, diabetes and chronic obstructive pulmonary disease. Only "chronic" patients who had at least 2 prescriptions within the same subgroup of drugs or specific medications during the year were selected for the analysis. A multidimensional measures of socio-economic position, declined in a national deprivation index at the municipality level, was used to identify and estimate the relationship with drug use indicators. The medicine consumption rate for each pharmacological category was estimated for prevalent users while adherence and persistence to pharmacologic therapy at 12 months were evaluated for new users. Results The results highlighted how the socioeconomic deprivation is strongly correlated with the use of medicines: after adjustment by deprivation index, the drug consumption rates decreased, mainly in the most disadvantaged areas, where consumption levels are on average higher than in other areas. On the other hand, the adherence and persistence indicators did not show the same trend. Conclusions This study showed that drug consumption is influenced by the level of deprivation consistently with the distribution of diseases. For this reason, the main levers on which it is necessary to act to reduce disparities in health status are mainly related to prevention. Moreover, it is worth pointing out that the use of a municipal deprivation indicator necessarily generates an ecological bias, however, the experience of the present study, which for the first-time deals with the complex and delicate issue of equity in Italian pharmaceutical assistance, sets the stage for new insights that could overcome the limits.